Comparison of the SphygmoCor XCEL device with applanation tonometry for pulse wave velocity and central blood pressure assessment in youth. Issue 1 (January 2019) - Stabouli, Stella; Printza, Nikoleta; Zervas, Chris; Dotis, John; Chrysaidou, Katerina; Maliahova, Olga; Antza, Christina; Papachristou, Fotios; Kotsis, Vasilios
Abstract : Background: Vascular phenotype by assessing carotid–femoral pulse wave velocity (cf-PWV) and central SBP (cSP) in the young could be used as an intermediate cardiovascular outcome measure. Tonometry is considered the gold-standard technique, but its use is challenging in clinical practice, especially when used in children. The purpose of this study was to validate cf-PWV and cSP assessment with novel oscillometric device (SphygmoCor XCEL) in children and adolescents. Methods: cf-PWV and cSP were measured in 72 children and adolescents aged 6–20 years. Measurements were performed by applanation tonometry and by the SphygmoCor XCEL device at the same visit under standardized conditions. Regression analysis and Bland–Altman plots were used for comparison of the tonometer-based with oscillometric-based method. Results: Mean cf-PWV measured by applanation tonometry was 4.85 ± 0.81 m/s and measured by SpygmoCor XCEL was 4.75 ± 0.81 m/s. The mean difference between the two devices was 0.09 ± 0.47 m/s ( P  = NS). cSP measured by SpygmoCor XCEL was strongly correlated with cSP measured by applanation tonometry ( R 2  = 0.87, P  < 0.001). Mean cSP measured by applanation tonometry was 103.23 ± 9.43 mmHg and measured by SpygmoCor XCEL was 103.54 ± 8.87 mmHg. The mean cSP difference between the two devices was −0.30 ± 3.34 mmHg ( P  = NS), and fulfilled the AAMI criterion 1. The estimated intersubject variability was 2.17 mmHg. Conclusion: The new oscillometric SphygmoCor XCEL device provides equivalent results for cf-PWV and cSP values to those obtained by tonometry in children and adolescents. Thus, the SphygmoCor XCEL device could be appropriate for assessing cf-PWV and cSP in the pediatric population. Abstract : Supplemental Digital Content is available in the text